2019
DOI: 10.3390/molecules24030600
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and Evaluation of Novel Transfersomes Combined with the Natural Antioxidant Resveratrol

Abstract: Resveratrol (tran-3,5,4′-trihydroxystibene, RSV) is a kind of polyphenol which has anti-inflammatory, antioxidant, anti-allergy, and anti-cancer properties, as well as being a scavenger of free radicals and preventing cardiovascular diseases. However, it is quite unstable in light, heat, and other conditions, and decays easily due to environmental factors. For these reasons, this study used a new type of carrier, transfersome, to encapsulate RSV. Transfersome consists of phosphatidyl choline (PC) from a liposo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
39
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(43 citation statements)
references
References 28 publications
3
39
0
1
Order By: Relevance
“…The resulting mixture is then homogenized using a high-pressure homogenizer. Finally, the transfersomes are stored in appropriate conditions [ 7 , 79 ].…”
Section: Preparation Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The resulting mixture is then homogenized using a high-pressure homogenizer. Finally, the transfersomes are stored in appropriate conditions [ 7 , 79 ].…”
Section: Preparation Methodsmentioning
confidence: 99%
“…In 2019, Wu et al prepared transfersomes combined with resveratrol using the high-pressure homogenization technique. It was found that the obtained transfersomes could improve the stability, bioavailability, solubility and safety of resveratrol [ 79 ].…”
Section: Applications Of Transfersomes As the Transdermal Deliverymentioning
confidence: 99%
“…Therefore, both T10 and T12 formulations were selected as the optimized green tea extract ethosomal formulations, that showed higher EE %, lower polydispersity index, as well as optimum release, consequently increasing penetrability and bioavailability [43].…”
Section: Fig 4: Release Profiles Of All the Prepared Ethosomes (Eachmentioning
confidence: 99%
“…In recent years several anti-inflammatory drugs such as baicalin [15], methotrexate [16], naringenin [17], resveratrol [18,19], and naproxen sodium [20] have been encapsulated in ultradeformable liposomes in order to reduce skin inflammation. The current study was focused on the co-encapsulation of two active compounds, naproxen sodium and idebenone, within ultradeformable liposomes, made up of two different edge activators, i.e., Tween ® 80 (T80), a hydrophilic non-ionic surfactant, and sodium deoxycholate (SDC), a steroid-like anionic surfactant (Formulations 1 and 2, respectively) in order to obtain a synergistic action and thus to potentiate the anti-inflammatory effect.…”
Section: Introductionmentioning
confidence: 99%